Immunohistochemical detection of chemokine receptor 4 expression in chronic osteomyelitis confirms specific uptake in 68Ga-Pentixafor-PET/CT - Bouter, Yvonne; Meller, Birgit; Sahlmann, Carsten O.; Wolf, Bettina J.; Langer, Laura; Bankstahl, Jens P.; Wester, Hans J.; Kropf, Saskia; Meller, Johannes; Bouter, Caroline (Nuklearmedizin - NuclearMedicine, 2018)
Previous findings of our group showed the chemokine receptor CXCR4 as a suitable target in PET/CT-imaging of axial bone infections, early postoperative osteomyelitis and periprosthetic infections. The aim of this study was to verify specific uptake of 68Ga-Pentixafor in chronic osteomyelitis. Methods: 29 consecutive patients who underwent 68Ga-Pentixafor-PET/CT with clinically suspected osteomyelitis were evaluated retrospectively. Bone tissues of 6 patients were available and evaluated by immunohistochemical staining for CXCR4 and autoradiography with 68Ga-Pentixafor. Staining was performed with an anti-CXCR4 antibody. In order to detect lymphocytic infiltration and CXCR4-expressing lymphocytes double immunofluorescence with an anti-CD3 and anti-CXCR4 antibody was performed. Results: 68Ga-Pentixafor-PET/ CT was true positive in 16 and true negative in 13 patients. In available bone tissue samples, immunohistochemical staining of CXCR4 expression and autoradiography with 68Ga-Pentixafor was highly positive. Double immunofluorescence was able to detect CXCR4-expressing T-lymphocytes within all bone samples while a control sample of noninfected tibial bone was negative for CXCR4. Conclusion: 68Ga-Pentixafor-PET/CT specifically shows CXCR4-expressing immune cells in chronic osteomyelitis and is therefore a suitable method for imaging chronic infection of the skeleton.Der Chemokinrezeptor CXCR4 konnte in einer Pilotstudie unserer Arbeitsgruppe als geeignete Zielstruktur zur PET/CT-Bildgebung von frühen postoperativen und periprothetischen Osteomyelitiden sowie Osteomyelitiden im Stammskelett identifiziert werden. In dieser Studie haben wir untersucht, ob 68Ga-Pentixafor spezifisch CXCR4-exprimierende Entzündungszellen in einer chronischen Osteomyelitis darstellen kann. Methoden: Es erfolgte eine retrospektive Auswertung von 29 Patienten mit klinischem Verdacht einer chronischen Osteomyelitis, die mittels 68Ga-Pentixafor-PET/CT untersucht wurden. Hiervon lagen uns in 6 Fällen Knochengewebe zur immunhistochemischen und autoradiographischen Evaluation vor. Die Immunhistochemie wurde mit einem anti-CXCR4 Antikörper durchgeführt. Des Weiteren wurden ein anti-CD3 und der anti-CXCR4-Antikörper zur Detektion CXCR4-exprimierender Lymphozyten am Ort der Entzündung mittels Doppel- Immunfluoreszenz verwendet. Ergebnisse: Die 68Ga-Pentixafor-PET/CT war bei 16 Patienten richtig positiv und bei 13 Patienten richtig negativ. Die Färbungen der verfügbaren Knochenpräparate waren sowohl in der Immunhistochemie als auch in der Autoradiographie deutlich positiv. In der Immunfluoreszenz konnten zudem CXCR4-exprimierende Lymphozyten am Ort der Entzündung in allen Proben nachgewiesen werden. Die Kontrolle eines Präparats einer nicht infizierten distalen Tibia zeigte dagegen keine CXCR4-oder CD3-Expression. Fazit: Mit der 68Ga-Pentixafor-PET/CT können spezifisch CXCR4-exprimierende Lymphozyten am Ort der Entzündung nachgewiesen werden. Die 68Ga-Pentixafor-PET/CT stellt eine geeignete Methode in der Diagnostik chronischer Osteomyeltiden dar.
Keywords: Osteomyelitis; PET/CT; pentixafor